Humans Created According to the Imago Dei: An Alternative Proposal: with Michael L. Spezio, “Social Neuroscience and Theistic Evolution: Intersubjectivity, Love, and the Social Sphere”; David Fergusson, “Humans Created According to the Imago Dei: An Alternative Proposal”; Thomas F. Tracy, “Divine Purpose and Evolutionary Processes”; Thomas Jay Oord, “The Divine Spirit as Causal and Personal”; and John W. Cooper, “Created for Everlasting Life: Can Theistic Evolution Provide an Adequate Christian Account of Human Nature?” - Fergusson, David (Zygon, 2013)
Classical approaches to the idea of the imago Dei in the theology of creation have tended to postulate a distinctive element of the human being not found in other creatures, with the possible exception of angels. This is often combined with attempts to use the imago concept as an organizing principle within Christian theology. Such approaches are now problematic not merely on account of their exegetical findings, but for methodological reasons. In light of recent exegesis, the imago Dei in Genesis 1:26–27 should be seen as a signifier of human life under God, rather than a single determining characteristic or essential attribute. Following the wisdom literature, the imago Dei can be understood, in a more diffused manner, as represented by human persons over long periods of evolutionary history in their characteristic quotidian forms of life, thus signifying the providential ordering of human life everywhere. The recent work of David Kelsey on theological anthropology is engaged in this context.